2021
DOI: 10.1101/2021.09.15.459697
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular architecture and dynamics of SARS-CoV-2 envelope by integrative modeling

Abstract: Despite tremendous efforts by research community during the COVID-19 pandemic, the exact structure of SARS-CoV-2 and related betacoronaviruses remains elusive. Here, we developed and applied an integrative multi-scale computational approach to model the envelope structure of SARS-CoV-2, focusing on studying the dynamic nature and molecular interactions of its most abundant, but largely understudied, M (membrane) protein. The molecular dynamics simulations allowed us to test the envelop stability under differen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 111 publications
1
11
0
Order By: Relevance
“…In this study, we used the CG model based on Martini 3 force field of SARS-CoV-2 envelope developed in [28], and kindly provided to us by W. Pezeshkian, D. Korkin and S.-J. Marrink (8 February 2022 version).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we used the CG model based on Martini 3 force field of SARS-CoV-2 envelope developed in [28], and kindly provided to us by W. Pezeshkian, D. Korkin and S.-J. Marrink (8 February 2022 version).…”
Section: Methodsmentioning
confidence: 99%
“…Among the advances in computational virology bringing us closer to creating realistic models of whole virions are: the study of the structural dynamics of viral capsids, by employing a coarse-graining (CG) molecular dynamics method [21]; atomic HIV-1 capsid model [22]; simulation of Herpes simplex virus type 2 B-capsid and chromatin models in GENeralized-Ensemble Simulation System (GENESIS) [23]; a dynamic and integrative computational model of an influenza A virion [24]; computational model of the envelope of the dengue virion [25]; Martini CG models of intact SARS-CoV and SARS-CoV-2 envelopes [26]; and multiscale CG models of the SARS-CoV-2 virion [27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with our previous simulation in which the only protein–protein interactions came from a few random contacts between unstructured loops. Since recent studies have suggested that M dimers actually do interact with each other, , we hypothesize that the lack of interactions in our simulation might be due to the simulation’s temperature of 300 K. This temperature is standard for molecular dynamics studies but is lower than human body temperature. Indeed, coarse-grained simulations by Rath et al suggest that lower temperatures might be detrimental to M protein dimer interactions, possibly due to an energy barrier from lipid packing around the dimers .…”
mentioning
confidence: 98%
“…4 While viral lysis was observed at high surfactant concentrations that can be cytotoxic, functional inactivation of viral proteins by surfactant adsorption was found at low surfactant concentrations suitable for therapeutic administration. 4 Despite recent great progress in molecular simulations of coronaviruses, including simulations of systems containing several to hundreds of millions of atoms, [14][15][16] no attempts have been made to study the interfacial interactions of SARS-CoV-2 virions with pulmonary and exogenous surfactants that is the focus of this work. Our main goal is to mimic in-silico surfactant adsorption on the S1 domain that is responsible for ACE2 binding.…”
mentioning
confidence: 99%